What were the Twin Towers? - O'Connor, Jim; Hammond, Ted (New York Grosset & Dunlap, an imprint of Penguin Random House, 2016)
"Discover the true story of the Twin Towers--how they came to be the tallest buildings in the world and why they were destroyed. When the Twin Towers were built in 1973, they were billed as an architectural wonder. At 1,368 feet, they clocked in as the tallest buildings in the world and changed the New York City skyline dramatically. Offices and corporations moved into the towers--also known as the World Trade Center--and the buildings were seen as the economic hub of the world. But on September 11, 2001, a terrorist attack toppled the towers and changed our nation forever. Discover the whole story of the Twin Towers--from their ambitious construction to their tragic end"--
Different countries
Includes bibliographical references (page 108)
1
Keywords: World Trade Center (New York, N.Y.) -- Juvenile literature; JUVENILE NONFICTION / Architecture; JUVENILE NONFICTION / History / United States / 20th Century; JUVENILE NONFICTION / History / United States / 21st Century; Skyscrapers -- New York (State) -- New York -- Juvenile literature; New York (N.Y.) -- Buildings, structures, etc -- Juvenile literature